2020
DOI: 10.1186/s12913-020-05730-4
|View full text |Cite
|
Sign up to set email alerts
|

Training health providers to address unhealthy alcohol use in primary care: a cross-sectional, multicenter study

Abstract: Background Health professionals’ training is a key element to address unhealthy alcohol use in Primary Care (PC). Education about alcohol use can be effective in improving PC provider’s knowledge and skills addressing alcohol-related problems. The aim of the study was to evaluate the training of health professionals to address unhealthy alcohol use in PC. Methods An observational, descriptive, cross-sectional, multicenter study was performed. Location: PC centres of the Spanish National Health System (SNHS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Therefore, it is important to know how to guide the high-risk patient to find solutions supporting their own health behavior, which facilitates coping with chronic diseases. Consequently, there is a need for sys tematic training to improve and support nurses' profes -sional competence in creating an innovative care plan, as well as empowering the patient to take more responsibility for their own health [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to know how to guide the high-risk patient to find solutions supporting their own health behavior, which facilitates coping with chronic diseases. Consequently, there is a need for sys tematic training to improve and support nurses' profes -sional competence in creating an innovative care plan, as well as empowering the patient to take more responsibility for their own health [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Interdisciplinary teamwork is at the heart of primary health care, especially in regard to treating multiple chronic conditions of the same patient, since they often need the help of different specialists at the same time. Training inter vention is essential in team training as it improves the team's clinical performance and effec tiveness as well as nurses' decisionmaking skills [13,14]. It can be assumed that the obtained results help clarify the need for training and related intervention may then be developed.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies reveal a specific lack of performance and management of patients with excessive alcohol consumption by PC professionals. 4 , 5 It has been found that professionals with a higher level of training in managing alcohol consumption were more confident in facing the related problems in their patients and used more appropriate strategies for patient management. 6 A systematic review reported that the main reasons for not addressing the patient at risk are lack of time, low self-confidence about their ability to perform screening tests and provide brief advice, and lack of training.…”
Section: Introductionmentioning
confidence: 99%
“…Many countries have their own safer drinking guidelines, but studies have reported that people do need the information to support them to make healthier choices. Motivation from healthcare providers can help patients in making behavioural changes towards making healthier choices or to abstain from alcohol (Romero-Rodríguez et al, 2020). But for influencing and motivating patients, providers require skills different from those used for managing patients with strictly medical problems.…”
Section: Introductionmentioning
confidence: 99%